ANALISIS PENENTUAN PENDAPATAN INDUSTRI KECIL BATIK (DESA PAKANDANGAN BARAT KABUPATEN SUMENEP) - Fathur Rahman; Arfida Boedirochminarni; Sudarti (Jurnal Ilmu Ekonomi JIE, 2020)
Economic growth should be directed in order to increase incomes and overcome economic disparities and social inequalities and also supported by an increase in productivity and efficiency and quality of human resources. Batik industry is one branch of the clothing and leather industry. One of the branches would observed by the author is a small batik industry, because batik is a traditional folk craft, which is one characteristic of Indonesian country and leather clothing industry branches that have a level of development prospective. This study aims to find out the factors wich affect the income of Small Batik Industry at West Pakandangan Village. Bluto sub district, Sumenep districts This study uses multiple linier regression analysis with primary data. The result show that the variable of capital (X1)significant positive effect of  0,000, labor (X2) significant positive effect of 0,001, total production (X3) significant positive effect of 0,055 and pattern share(X4) significant positive effect of 0,000 has simultaneously positive effect and significant to income. For individual, capital variable has no effect and significant at the income of Small Batik Industry at West Pakandangan Village. Bluto sub district, Sumenep districts